Estimation of Urinary Biomarker 8- OHDG in OP Pesticide Sprayers of Krishna and Guntur Districts - Sravanthi Malempati; Durga Rao B.V.; Basaveswara Rao M.V. (International Journal of Research in Chemistry and Environment (IJRCE), 2017)
Organophosphate pesticides can generate reactive oxygen species on DNA (both in the nucleus and mitochondria) causes a number of oxidative DNA lesions, results an oxidized form of guanosine, 8-OHdG. Exposure to pesticides both environmentally and occupationally causes a range of human health problems. It is estimated, worldwide that nearly 10,000 deaths result annually the use of chemical pesticides, with about three-fourths occurring in developing countries The main objective of the study was to evaluate the biochemical levels of 8-OHdG in spot urinary samples under the exposed OP pesticide sprayers and farm workers.